The influence of financial awareness and digital payment behavior on the financial management of UINSU students in the cashless era - Rushel Hardi; Muhammad Irwan Padli Nasution; Aqwa Naser Daulay (Indonesia Auditing Research Journal, 2026)
This research was conducted to examine the effects of financial awareness and digital payment behavior on the financial management of students at the Faculty of Islamic Economics and Business, State Islamic University of North Sumatra. A quantitative approach with an associative research design was employed in this study. The research population comprised 4,556 students, from which 98 respondents were selected using the Slovin formula and purposive sampling technique. Data were gathered through questionnaires and subsequently analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that financial awareness positively and significantly influences students’ financial management, as indicated by a regression coefficient of 0.336 and a significance value below 0.001. Likewise, digital payment behavior was found to have a positive and significant impact on financial management, with a regression coefficient of 0.474 and a significance value below 0.001. The simultaneous test further demonstrates that financial awareness and digital payment behavior jointly exert a significant influence on students’ financial management, as evidenced by an F-value of 69.603 and a significance level below 0.001. Furthermore, the coefficient of determination (R²) of 0.594 shows that 59.4% of the variance in students’ financial management can be explained by the two independent variables examined in this study.